2018
DOI: 10.1002/2017ja024681
|View full text |Cite
|
Sign up to set email alerts
|

MMS Examination of FTEs at the Earth's Subsolar Magnetopause

Abstract: Determining the magnetic field structure, electric currents, and plasma distributions within flux transfer event (FTE)‐type flux ropes is critical to the understanding of their origin, evolution, and dynamics. Here the Magnetospheric Multiscale mission's high‐resolution magnetic field and plasma measurements are used to identify FTEs in the vicinity of the subsolar magnetopause. The constant‐α flux rope model is used to identify quasi‐force free flux ropes and to infer the size, the core magnetic field strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(128 citation statements)
references
References 113 publications
10
117
1
Order By: Relevance
“…These results suggest that the newly formed ion-scale flux ropes have already demonstrated distinct properties in the magnetic structures and plasma features. Previous studies suggested that flux ropes containing less particles and stronger core fields reached a later stage of the evolution (e.g., Akhavan-Tafti et al, 2018 ;Chen et al, 2017 ;Ma et al, 1994), which may suggest that the quasi-2-D flux ropes in this study are in the later stage of evolution than the quasi-1-D flux ropes. The quasi-2-D flux ropes were observed in regions with a larger dawn-dusk field (~0.33) than the quasi-1-D flux ropes (~0.15; Figures 4f and 4g), which suggests that magnetic reconnections under these different magnetic field conditions might have given rise to the two different groups of ion-scale flux ropes.…”
Section: Conclusion and Discussionmentioning
confidence: 49%
“…These results suggest that the newly formed ion-scale flux ropes have already demonstrated distinct properties in the magnetic structures and plasma features. Previous studies suggested that flux ropes containing less particles and stronger core fields reached a later stage of the evolution (e.g., Akhavan-Tafti et al, 2018 ;Chen et al, 2017 ;Ma et al, 1994), which may suggest that the quasi-2-D flux ropes in this study are in the later stage of evolution than the quasi-1-D flux ropes. The quasi-2-D flux ropes were observed in regions with a larger dawn-dusk field (~0.33) than the quasi-1-D flux ropes (~0.15; Figures 4f and 4g), which suggests that magnetic reconnections under these different magnetic field conditions might have given rise to the two different groups of ion-scale flux ropes.…”
Section: Conclusion and Discussionmentioning
confidence: 49%
“…Our event selection criteria only allow FTEs with (1) small impact parameter (IP < 0.5) and (2) cylindrical symmetry (force‐free model goodness of fit parameter, χ 2 < 0.1; cf. Akhavan‐Tafti et al, ). A complete list of all 63 burst‐mode FTEs used in this study and the force‐free flux rope model results are provided in Table S1 in the supporting information.…”
Section: Methodsmentioning
confidence: 99%
“…Further, the fitting method determines the impact parameter (i.e., closest approach -Tafti et al, 2018;DiBraccio et al, 2015;Slavin et al, 2003). They were detected based on their bipolar signature in the maximum variance component of the local magnetic field (B max ) coinciding with a peak in both the intermediate variance component of magnetic field (B int ) and |B|.…”
Section: Ddm Flux Transfer Eventsmentioning
confidence: 99%
“…Only structures that satisfy the following criteria are included in the FTE statistics for the DDM events: (i) impact parameter <0.5, (ii) chi-square value <0.1 (see Akhavan-Tafti et al, 2018), and (iii) FTE radius <2,500 km. In addition, the use of the force-free model enables a nonbiased investigation of magnetic structures at the magnetopause.…”
Section: Ddm Flux Transfer Eventsmentioning
confidence: 99%